A risk-based approach for the design of rock slopes subject to multiple failure modes—illustrated by a case study in Hong Kong - Pine, R.J.; Roberds, W.J. (International journal of rock mechanics and mining sciences (Oxford, England : 1997), 2005)
The widening of the Tuen Mun Road highway in Hong Kong involved construction and subsequent operation in an area of steep rock slopes above a heavily trafficked six lane highway. A risk-based approach to slope design was required by the authorities. The approach that was developed is described in detail and includes consideration of risk acceptance criteria, consequence analysis, effects of traffic characteristics, likelihood of slope failure and overall risk and risk allocation. Based on statistical data for slope failures in Hong Kong, world-wide data on dam failures and some engineering judgement, a relation was estimated between annual probability of slope failure and design factor of safety. The implementation of the design involved allocation of acceptable levels of risk to different sections of slope and different modes of slope failure such that the summation of all risk was less than an expected fatality rate of 0.01 deaths per year per 500 m section of slope. This level of risk was determined in relation to objective standards for industrial facilities generally as defined by Hong Kong Planning Guidance criteria (Hong Kong Planning Standards and Guidelines, Hong Kong Planning Department, 1996 (Chapter 11)). These risks were converted into design factors of safety using the likely numbers of failures per mode and per section (more possible failures means that each possible failure location requires a higher factor of safety to achieve the overall risk objectives). Required design factors of safety from this approach were typically in the range 1.2–1.8 compared with a normal requirement in Hong Kong of 1.4.